Counselor Education in Technicolor: Recruiting Graduate Students of Color - Hipolito-Delgado, Carlos; Estrada, Diane; Garcia, Marina (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The dearth of ethnic diversity in the counseling field requires increased attention to strategies for recruiting graduate students of color. A case study of graduate students of color was conducted to identify factors that encouraged and discouraged them from pursuing careers in counseling. The participants in this study indicated that diversifying the counseling field, exposure to helping professionals, location of the graduate program, lack of student diversity, and program admissions requirements influenced their decision to pursue graduate degrees in counseling. Based on the findings of this study, implications for recruiting graduate students of color into counselor education programs include the need for graduate programs to demonstrate a commitment to diversity, increased clarity in admissions requirements, and providing students with guidance through the admissions process.